Effects of Swimming-Specific Repeated-Sprint Training in Hypoxia Training in Swimmers - Camacho-Cardenosa, Marta; Camacho-Cardenosa, Alba; González-Custodio, Adrián; Zapata, Víctor; Olcina, Guillermo (Frontiers in Sports and Active Living, 2020)
The aim of this study was to investigate the effect of a 4-wk in-water swimming-specific repeated-sprint training in hypoxia (RSH) compared to similar training in normoxia (RSN). Following a repeated-measures, counterbalanced cross-over design, 10 swimmers were requested to perform two trials consisting of in-water repeated sprints in hypoxic (RSH, simulated 4,040 m; FiO2 = 13.7%) or normoxic (RSN, 459 m, FiO2 calibrated= 20.9%) conditions. In both conditions, 8 additional exercise including 3 sets of 5 x 15 m “all-out” sprints (corresponding to a total of 625 m), with 20 s of passive recovery between efforts and 200 m of easy swimming between sets were included at the end of their swimming program over a 4-wk period. Hypoxic condition was generated using a simulator pumping air with lowered oxygen concentration into a facial mask. An incremental maximal test on an ergocycle, as well as 100 m and 400 m freestyle swimming performance (real competition format) were assessed before (pre), 7 days (post-1) and 2 weeks (post-2) after intervention. During training, heart rate (HR) and oxygen saturation (SpO2) were monitored. RSH showed significantly lower SpO2 (70.1±4.8 % vs. 96.1±2.7%, P < 0.01), concomitant with higher mean HR (159±11 bmp vs. 141±6 bmp, P<0.01) than RSN. No significant changes in maximal oxygen uptake, other submaximal physiological parameters, 100 m or 400 m swimming performances were found. Although providing additional physiological stress, performing in-water repeated-sprint training in hypoxia does not provide evidence for higher benefits than similar training in normoxia to improve swimmers performance.